Pola Komunikasi Penulis dan Pembaca Alternative Universe “Triple A” (Studi Kasus pada Akun X @kyuniverce) - Sari, Dian Puspita; Hindra Hastuti, Nurnawati; Maserona, Lukas (Solidaritas, 2024)
After the pandemic, Alternative Universe (AU) fiction has become a new trend among Generation Z. The @kyuniverce account is one of the Alternative Universe writers who often interacts with their readers. This research aims to find out the communication patterns of Alternative Universe “Triple A” writers and readers. The theory used is the theory of mass communication by McQuail. The research method used is descriptive qualitative with purposive sampling technique. To analyze the communication patterns used, researchers presented 6 informants where 1 person was a writer and 5 people were readers. The results of this study indicate the existence of two communication patterns on the @kyuniverce account, namely circular communication patterns, where there must be feedback to each other, as well as broker communication patterns, where the recipient of the message can choose to continue the message or not. Keyword : Alternative Universe, X, a Pattern of Communication